Inhibitory effect of THPGV-0 on the histamine release from antigen-induced RBL-2H3 cells - Agung Endro Nugroho; Ritmaleni Ritmaleni; Novrizal Abdi Sahid; Kazutaka Maeyama (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Tetrahydropentagamavunon-0 (THPGV-0) is assumed to be main metabolite product of biotransformation process of PGV-0. THPGV-0 was synthesized by converting PGV-0 to the compound by hydrogenation with Pd/C as a catalyst. PGV-0 potently inhibited the histamine release from rat mast cells in vitro and in vivo, however, ironically only traces amount of compound was found in the blood. THPGV-0 is assumed to have important roles in the biological effects of PGV-0 in vivo. In present study, we investigated the antiallergy effect of THPGV-0 in compare to this of PGV-0 in vitro. The study was performed by using rat basophilic leukemia (RBL-2H3) cell line, a tumor analog of mucosal mast cells. DNP-BSA, an antigen, was used as an inducer for stimulating the histamine release from mast cells. In present study, THPGV-0 at low concentration did not succeed to inhibit the histamine release, but at higher concentration (30 and 100 M) showed strong effects. THPGV-0 at concentration of 100 M depleted the histamine release by 96.10 0.51%. In compare to PGV-0, THPGV-0 has higher efficacy but less potent. In the study, the possibilities of the spontaneous release from RBL-2H3 cells by the compounds were also observed. All concentrations of THPGV-0 as well as PGV-0 showed low spontaneous histamine release, less than 10 % of the total histamine contained in RBL-2H3 cells.Key words: tetrahydropentagamavunon-0, allergy, histamine, RBL-2H3 cells